2019
DOI: 10.1038/s41598-018-38015-2
|View full text |Cite
|
Sign up to set email alerts
|

Environmental stresses suppress nonsense-mediated mRNA decay (NMD) and affect cells by stabilizing NMD-targeted gene expression

Abstract: Nonsense-mediated mRNA decay (NMD) is a cellular mechanism that eliminates mRNAs that harbor premature translation termination codons (PTCs). Here, we investigated the effects of environmental stresses (oxidative stress and endoplasmic reticulum (ER) stress) on NMD activity. Methylmercury (MeHg) was used to cause oxidative stress and thapsigargin to stress the ER. NMD suppression, evidenced by upregulation of NMD-sensitive mRNAs and a decrease in UPF1 phosphorylation, was observed in MeHg-treated myogenic cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 48 publications
0
15
0
Order By: Relevance
“…14 Nonsense-mediated mRNA decay (NMD) is an evolutionarily conserved, translation-dependent RNA surveillance mechanism that recognizes and degrades PTC-and other error-containing transcripts as well as many naturally occurring, error-free transcripts. The ability of NMD to also target "normal" mRNA transcripts is important for a wide range of physiological pathways including differentiation and proliferation, 15,16 development, [17][18][19][20] viral defense, 21,22 stress response, [23][24][25] and neuronal activity (eg, synaptic plasticity and axonal guidance). [26][27][28] NMD machinery consists of several core factors that were first discovered in yeast as the up-frameshift-1 (Upf1), Upf2, and Upf3 genes.…”
Section: Contextual Backgroundmentioning
confidence: 99%
“…14 Nonsense-mediated mRNA decay (NMD) is an evolutionarily conserved, translation-dependent RNA surveillance mechanism that recognizes and degrades PTC-and other error-containing transcripts as well as many naturally occurring, error-free transcripts. The ability of NMD to also target "normal" mRNA transcripts is important for a wide range of physiological pathways including differentiation and proliferation, 15,16 development, [17][18][19][20] viral defense, 21,22 stress response, [23][24][25] and neuronal activity (eg, synaptic plasticity and axonal guidance). [26][27][28] NMD machinery consists of several core factors that were first discovered in yeast as the up-frameshift-1 (Upf1), Upf2, and Upf3 genes.…”
Section: Contextual Backgroundmentioning
confidence: 99%
“…We propose that there might be two main reasons for the inconsistent expression trend of UPF1 in different cancers. Firstly, it was reported that oxidative stress and endoplasmic reticulum (ER) stress could suppress NMD through the phospho-eIF2α/ATF4 pathway [ 54 ]. This might explain the low expression of UPF1 in renal cancer, which has feature enhanced oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…One possibility is that defective spliceosome formation causes abnormal mRNAs, which subsequently promote nonsense-mediated mRNA decay (NMD). Considering that PERK expression is involved in NMD suppression,[ 55 , 56 ] the over-activated NMD possibly induces downregulation of PERK. The underlying mechanism between DGCR14 and PERK will be the next primary question for a future study.…”
Section: Discussionmentioning
confidence: 99%